2012
DOI: 10.1002/mrm.24186
|View full text |Cite
|
Sign up to set email alerts
|

Clinically compatible MRI strategies for discriminating bound and pore water in cortical bone

Abstract: Advances in modern MRI pulse sequences have enabled clinically-practical cortical bone imaging. Human cortical bone is known to contain a distribution of T1 and T2 components attributed to bound and pore water, although clinical imaging approaches have yet to discriminate bound from pore water on the basis of their relaxation properties. Herein, two clinically-compatible MRI strategies are proposed for selectively imaging either bound or pore water by utilizing differences in their T1s and T2s. The strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(198 citation statements)
references
References 37 publications
12
181
5
Order By: Relevance
“…However, it is necessary to distinguish between the bound and pore water signals, because their sum has little or no relationship to mechanical properties (20). Bound and pore water signals can be discriminated on the basis of relaxation times by using wide-bandwidth T2-selective adiabatic radiofrequency (RF) pulses (21). Use of these pulses in conjunction with an ultrashort echo time (UTE) acquisition allows imaging of bound and pore water signal (22).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is necessary to distinguish between the bound and pore water signals, because their sum has little or no relationship to mechanical properties (20). Bound and pore water signals can be discriminated on the basis of relaxation times by using wide-bandwidth T2-selective adiabatic radiofrequency (RF) pulses (21). Use of these pulses in conjunction with an ultrashort echo time (UTE) acquisition allows imaging of bound and pore water signal (22).…”
Section: Subjectsmentioning
confidence: 99%
“…The pulse sequence diagram for these sequences is given in Figure 1. Signal equations and a more detailed description of these methods can be found in prior works (21,22).…”
Section: Subjectsmentioning
confidence: 99%
“…There are few reports on the association of peaks from T 2 distributions measured on rats' femurs. Horch et al [17,18] showed that, for human cortical bone, the T 2 values under millisecond correspond to bound water (primary to collagen) while the T 2 values larger than 1 ms (up to 1 s) correspond to pore water and lipids (bone marrow). Moreover, the majority of studies on human cortical bone are focused on the association of ultrashort T 2 values to collagen methylene protons (150 ms ≤ T 2 ≤ 1 ms), collagen-bound water protons (50 ms ≤ T 2 ≤ 1 ms) water protons in pores in lipid protons (1 ms ≤ T 2 ≤ 1 s) [16].…”
Section: The Effect Of Lipid-lowering Drugs Evaluated From T 2 Distrimentioning
confidence: 99%
“…The 1 H CPMG (CarrPurcell-Meiboom-Gill) pulse sequence is a NMR method which correlated with Laplace inversion analysis lead to a relaxation T 2 spectrum that can be used to determine the porosity and to assess the pore size distribution in bone [10]. There are just a few studies by NMR spectroscopy [11] or relaxometry [12] on rats' bones or rat optical nerve and frog sciatic nerve [13], but there are many studies of human cortical bone by 1 H NMR relaxometry in particular 1D T 2 distribution [14][15][16][17][18][19] or 2D T 2 -T 2 exchange maps [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This is done by inverting the longitudinal magnetization of the long T 2 signal components (i.e., muscle and bone marrow fat) while saturating the signal from cortical bone [27][28][29][30][31]. The Cones acquisition starts after an inversion time (TI) delay, which is used to null the long T 2 ⁎ components while permitting detection of recovered cortical bone signal (Fig.…”
Section: Pulse Sequencementioning
confidence: 99%